2013
DOI: 10.1074/jbc.m113.470500
|View full text |Cite
|
Sign up to set email alerts
|

RNF185 Is a Novel E3 Ligase of Endoplasmic Reticulum-associated Degradation (ERAD) That Targets Cystic Fibrosis Transmembrane Conductance Regulator (CFTR)

Abstract: Background: RNF5 is an ERAD E3 ligase targeting CFTR to co-translational degradation, and RNF185 is an RNF5 homolog. Results: RNF185 targets CFTR and CFTR⌬F508 to co-translational degradation and synergizes with RNF5 to their posttranslational degradation. Conclusion: RNF185 and RNF5 act together as major ERAD E3 ligases of CFTR. Significance: The RNF5/RNF185 module is a new potential therapeutic target for the treatment of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 72 publications
2
82
2
Order By: Relevance
“…The Hrd1 targets the ER luminal and integral membrane proteins harboring folding defects in either their ER luminal or their transmembrane regions, while the Doa1 targets integral membrane proteins with lesions in their cytosolic domains (Bays et al, 2001;Bordallo et al, 1998;Kikkert et al, 2004;Swanson et al, 2001). The mammalian cells posses a large set of ERAD ligases that localize in the ER membrane or in the cytosol (or in both) (Bagola et al, 2011;El Khouri et al, 2013). It was proposed that the ERAD substrates are extracted from the ER by three different ways: 1.…”
Section: The Endoplasmic Reticulum-associated Degradationmentioning
confidence: 99%
“…The Hrd1 targets the ER luminal and integral membrane proteins harboring folding defects in either their ER luminal or their transmembrane regions, while the Doa1 targets integral membrane proteins with lesions in their cytosolic domains (Bays et al, 2001;Bordallo et al, 1998;Kikkert et al, 2004;Swanson et al, 2001). The mammalian cells posses a large set of ERAD ligases that localize in the ER membrane or in the cytosol (or in both) (Bagola et al, 2011;El Khouri et al, 2013). It was proposed that the ERAD substrates are extracted from the ER by three different ways: 1.…”
Section: The Endoplasmic Reticulum-associated Degradationmentioning
confidence: 99%
“…Previous studies demonstrate that ubiquitination is pivotal for ΔF508-CFTR ER associated protein degradation (ERAD) by multiple Ub E3 ligases, including Rma1 (Younger et al, 2006), Gp78 (Morito et al, 2008), RNF185 (El Khouri et al, 2013), Ubr1 (Stolz et al, 2013) and the chaperone-associated CHIP (Meacham et al, 2001). Recent ΔF508-CFTR interactome and CFTR correction-related transcriptome analysis identified several E3 ligases (TRIM21, UBR4, RNF215, UBOX5, ASB8, FBXO7, SYVN1 and FBXO2) that could facilitate the ERAD in CF bronchial epithelia (Hegde et al, 2015; Pankow et al, 2015; Ramachandran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Praticò AD have previously reported that mutations of the CFTR genotype: F508/12TG‐5T and 470MV correlate with liver disease of cystic fibrosis patients, suggesting that CFTR might be involved in liver damage [Pratico et al, ]. Furthermore, an association between CFTR and ER stress has been suggested based on the central role of the ER in membrane protein synthesis [El Khouri et al, ]. Moreover, it was reported that cystic fibrosis patients with mutations in the CFTR gene that engage the ER quality control system and hence unfolded protein response signaling are 20‐fold more likely to develop diabetes than patients with other types of CFTR mutations in cystic fibrosis‐related diabetes [Ali, ].…”
mentioning
confidence: 99%